On the Monitoring Complex Multivariate Processes - Rajda-Tasior, Angelina; Kończak, Grzegorz (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
This article presents a proposal of the method of monitoring complex multidimensional processes. The problem relates to monitoring the quality of production with some attribute variables when the production is performed by some operators. To describe the quality status we used the matrix in which elements are the numbers of defective units. The proposed method uses permutation tests. The "out-of-order" signal is obtained by comparing the matrix in period t to the matrix from stable process. The test statistic used in permutation test is based on a function of distance between matrices. The properties of the proposed method have been described using computer simulation.